2016
DOI: 10.3892/ijo.2016.3533
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-223 inhibits epithelial-mesenchymal transition in gastric carcinoma cells via Sp1

Abstract: Abstract. Sp1 plays critical roles in epithelial-mesenchymal transition (EMT) of certain cancer. However, few studies have indicated whether Sp1 is involved in the EMT of gastric cancer, and whether abnormal expression of Sp1 in gastric cancer EMT is regulated in a post-transcriptional manner, and the involvement of miRNAs in this regulation. In this study, we selected 20 cases of gastric cancers, their liver metastases and para-carcinoma tissues to examine the levels of Sp1 protein and mRNA by immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The transcription factor specificity protein 1 (Sp1) is widely involved in cancer cell proliferation, migration, and invasion . Recently, it was reported that Sp1 might be related to the activation of Wnt/β‐catenin signaling and the induction of the EMT process through genetic regulation . To identify whether DMBA induced cell proliferation and migration through Sp1 regulation, we investigated the influence of DMBA on Sp1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor specificity protein 1 (Sp1) is widely involved in cancer cell proliferation, migration, and invasion . Recently, it was reported that Sp1 might be related to the activation of Wnt/β‐catenin signaling and the induction of the EMT process through genetic regulation . To identify whether DMBA induced cell proliferation and migration through Sp1 regulation, we investigated the influence of DMBA on Sp1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…reported that Sp1 might be related to the activation of Wnt/b-catenin signaling and the induction of the EMT process through genetic regulation [49][50][51]. To identify whether DMBA induced cell proliferation and migration through Sp1 regulation, we investigated the influence of DMBA on Sp1 expression.…”
mentioning
confidence: 99%
“…Accumulating evidence has demonstrated that miRNAs are involved in cell proliferation, migration, and invasion in malignancy, such as lung cancer bone metastasis 11,13,14,17,19 . For instance, HE et al 29 revealed that downregulation of miR-20b may dramatically suppress H22 cell proliferation by directly targeting PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miRNAs are implicated in various cellular processes [13][14][15] . In addition, many studies have already demonstrated that miRNA dysfunction is involved in the occurrence and progression of malignancies, such as breast cancer, gastric carcinoma, prostate cancer, and lung cancer [16][17][18][19] . In recent years, various studies have shown that miR-192-5p is significantly downregulated in malignant carcinoma, while miR-192-5p overexpression may play a potential role in suppressing tumourigenesis through different mechanisms 20,21 .…”
mentioning
confidence: 99%
“…In PC, the first large-scale study with microRNAs analysis was conducted by Zhang et al, (2015), and some differentially expressed microRNAs were identified, such as miR-107, and miR-223-3p. These micro RNAs were described related with metastasis, invasion, transport, and colonization in cancer (Gao et al, 2016;Hu et al, 2016;Markou et al, 2016;Mavrakis et al, 2011). Since PC is often accompanied with lymph node metastases, the involvement of these miRNAs in prognosis of this disease was checked.…”
Section: Introductionmentioning
confidence: 99%